Severe acute thinner intoxication - Akısü, Mete; Mir, Sevgi; Genç, Berhan; Cura, Alphan (The Turkish Journal of Pediatrics, 1996)
Thinner which contains aromatic hydrocarbons such as xylene, toluene and N-hexane is widely used in industrial plants manufacturing dyes, plastic, varnishes and glues. Chronic intoxication due to abuse of solvents, including thinner, by workers who inhale the solvent vapor is frequently encountered. Acute intoxication with ingestion of excessive amounts is relatively rare and usually fatal. It is reported that 45-50 ml of orally ingested thinner is enough to cause severe complications. The case reported here was forced to drink 200 ml of thinner by an older friend, and presented with severe complications such as rhabdomyolysis, polyneuropathy, chemical pneumonia and coma. To the best of our knowledge this is the first case reported in the literature to survive acute thinner intoxication with such complications.